Morpho-physiological and anatomical character changes of rice under waterlogged and water-saturated acidic and high Fe content soil - Turhadi, T.; Hamim, H.; Ghulamahdi, Munif; Miftahudin, M. (Penerbit Universiti Kebangsaan Malaysia, 2020)
Waterlogging is one of the limiting factors in crop cultivation. Moreover, high iron (Fe) content in acidic soils could also disturb plant growth. However, there is limited scientific information of morpho-physiological and anatomical responses of rice grown in waterlogged acidic soils with high Fe. Therefore, the objective of the research was to investigate the morpho-physiological and anatomical responses of rice to waterlogged and water-saturated soil condition in acidic soil with high Fe. Morpho-physiological and anatomical characters of rice were evaluated. The results showed that the waterlogging in acidic and high Fe content soil disturbed the rice growth as indicated by the change of morpho-physiological and anatomical characters. The water-saturated soil showed better condition for rice cultivation than that of waterlogging. The plant biomass, root anatomical, lipid peroxidation level, Fe absorption, and leaf gas exchange parameter could be evidences of changes in rice under both conditions. Based on the waterlogging tolerance coefficient (WTC), we proposed shoot and root dry weight, cortex thickness, and Fe content in shoot as screening tools for waterlogging tolerance of rice in acidic and high Fe content soil. The finding offers insight about waterlogged condition in acidic and high Fe soil could be restored in crop cultivation.